Single antenna power measurements based direction finding : an FRI solution - Zhang, Song Bai (2010)
Determining the angle of arrival (AoA) for wireless source signals has great poten- tial practical applications, one example is beam forming in cellular communication. The conventional methodology used to determine the AoA mainly uses the an- tenna array as an acquisition system, and there are many signal process algorithms developed to retrieve the direction of arrival information. The whole system also brings high hardware cost and expensive computational complexity. In this Final Year Project report, a new method based on the single antenna power measure- ments and sparse sampling theory is presented. Throughout series of calculations and simulation results in this report, our proposed method is capable to reduce the cost and computational complexity for AoA nding while maintaining its ac- curacy for practical applications. This report starts with brief review of conventional AoA nding algorithms, and explicitly explain the most famous MUSIC algorithm. After that, the idea of sparse sampling theory (sampling with nite rate of innovation) is discussed, which serves as the keystone of our presented algorithm. With all this background in- formation, overall mathematical formulation for this project is presented. In the formulation process, by taking the band limited approximation of antenna pat- tern, we shall formulate AoA nding problem into Finite Rate of Innovation (FRI) framework. Followed by the formulation, performance of Minimum Description Length is dis- cussed for estimating the number of source signals. The idea and simulation results on deploying Cadzow's Signal Enhancement algorithm to improve AoA nding accuracy are proposed and evaluated. To further reduce the computational com- plexity, design of ideal low pass lter is explored, besides that, Conjugate Gradient Method for frequency spectrum estimation based on non-uniform sampling in time domain is also presented at last part of this report.